The ambush of Gameth in Barbacha - AIT MEDDOUR , Mahmoud (The Algerian Historical Journal, 2026)
The article recounts the course of one of the events that Barbacha had known during the war of national liberation. This is the Gameth ambush in the Barbacha region southeast of Bejaia. This fact is often spoken of by the people of the region, narrated, and transmitted orally based on the testimonies of the mujahidin or witnesses with versions often diametrically opposed. This is logical given the complexity of tracing the course of a fact after several years by elderly people whose many memories had disappeared with age and the difficulty of situating the facts told in a more precise historical context.